Effects of intermittent usage of water-based neomycin sulfate on the growth performance of weanling pigs - Gottlob, R.O.; Neill, C.R.; Groesbeck, C.N.; Brown, K.R.; Frantz, N.Z.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 360 weanling pigs (initially 11.4 lb and 18 ± 3 d of age, PIC) were used to determine the effects of intermittent use of water-based medication on nursery pig growth performance. Pigs were given one of eight experimental treatments: negative control (no antibiotics in the feed or water); positive control with Neo-Terramycin® in the feed (140 g/ton Neomycin sulfate, 140 g/ton Oxytetracycline HCl); continuous use of either 38.0 or 75.5 mg Neomycin sulfate per L of water; use of either 38.0 or 75.5 mg of Neomycin sulfate per L of water, during weeks 1 and 3 after weaning; and use of either 38.0 or 75.5 mg Neomycin sulfate per L of water during weeks 2 and 4 after weaning. Overall (d 0 to 28 after weaning), pigs provided Neomycin sulfate in the water continuously and pigs fed the positive control diet had greater ADG (P<0.05) and ADFI (P<0.04) than did pigs provided non-medicated water and feed. Pigs fed the positive control diet tended (P<0.15) to have greater ADG than did pigs provided an intermittent supply of water-based Neomycin sulfate, but there was no difference in growth performance and feed efficiency between pigs fed the positive control diet and those provided a continuous supply of water-based Neomycin sulfate. Pigs provided a continuous supply of either dosage of Neomycin sulfate in the water had greater (P<0.05) ADG and ADFI than did pigs provided water-based Neomycin sulfate on an intermittent basis. These data demonstrate that providing neomycin in the feed or water results in a growth response, but there is no carryover effect. Thus, pig performance returns to the control level immediately after the supply of Neomycin is removed.
Swine research, 2005 is known as Swine day, 2005
Keywords: Nursery pig; Antibiotics; Water; Growth; Swine